2018
DOI: 10.1002/jlcr.3666
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in heterocycle labeling with carbon isotopes

Abstract: Heterocycles play an essential role in modern pharmaceutical and agrochemical developments, representing a very common structural unit in marketed drugs. Over the 46 new drugs approved in 2017 by the FDA, 25 contain in their structure a heterocyclic core. The development of novel and straightforward labeling strategies for the effective insertion of carbon isotopes into heterocylic scaffolds is an inspiring and vibrant field of research. The use of carbon-11, carbon-13, and carbon-14 isotopes is well establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In view of the fact that heterocycles play an important role in pharmaceuticals, much effort has been directed towards the formation of isotopically labeled derivatives, and developing routes that utilize CO 2 has been emphasized . Therefore, we have also demonstrated that the reaction of D 2 C­(OSiPh 3 ) 2 with N -methyl-1,2-phenylenediamine in DMSO affords N -methylbenzimidazole- d 1 . , In addition, 2 H NMR spectroscopy demonstrates that the formal oxidation of the [CH 2 ] moiety is achieved by the formation of water, in accord with the aforementioned ability of DMSO to act as an oxidizing agent …”
Section: Resultsmentioning
confidence: 80%
“…In view of the fact that heterocycles play an important role in pharmaceuticals, much effort has been directed towards the formation of isotopically labeled derivatives, and developing routes that utilize CO 2 has been emphasized . Therefore, we have also demonstrated that the reaction of D 2 C­(OSiPh 3 ) 2 with N -methyl-1,2-phenylenediamine in DMSO affords N -methylbenzimidazole- d 1 . , In addition, 2 H NMR spectroscopy demonstrates that the formal oxidation of the [CH 2 ] moiety is achieved by the formation of water, in accord with the aforementioned ability of DMSO to act as an oxidizing agent …”
Section: Resultsmentioning
confidence: 80%
“…Urea derivatives are common functional groups in medicinal chemistry and are often found in pharmaceuticals. , In 2018, Hesk and co-workers at Merck applied a strategy, published a few years earlier, for the labeling of 7 , a potent inhibitor of the NPY 5 receptor . A trapping of radioactive carbon dioxide by the aniline 5 under basic conditions, followed by an addition of POCl 3 as a dehydrating agent, led to the generation of an isocyanate intermediate.…”
Section: Radiocarbon Labelingmentioning
confidence: 99%
“…14 N can compensate for 15 N. There is no stable isotope of negative NMM for C to compensate for 13 C incorporation. Although recently scientists observed the ability of unstable 11 C (with negative NMM) in 11 CO2 to directly insert into carbonates unlike 12 C (with null NMM) and 13 C (with positive NMM) [25]. There is no stable isotope of positive NMM of O to counter by LeChatelier Principle the negative NMMs as 17 O is deposited within systems.…”
Section: Other Important Systems Of Applications Of Novel Phenomena B...mentioning
confidence: 99%
“…Such gravitational fields in hidden ways stimulate novel chemistry, optics, thermodynamics, transport, and transmutations within the nanobaths and of the nanobaths. In these effects of gravity on life, the author discloses that gravity is a force that caused the organization of life on earth by self-activation of clustering of organic molecules forming biomolecules having elements with stable isotopes of nonzero NMMs like: 1 H, 2 D, 13 C, 14 N, 15 N, 17 O, 25 Mg, 31 P and 33 S and other elements in essential minerals having nonzero NMMs. This notion is not proven but follows from the author's theory.…”
Section: Communication Between Various Systems In Cells and Living Or...mentioning
confidence: 99%